v = 3 and w = -7
1) We can solve this System of equations algebraically, i.e. without graphing:
2v +6w = -36
5v +2w = 1
2) We can use the Elimination Method to eliminate one variable and then add it up to the second one:
2v +6w = -36
5v +2w = 1 x(-3) Multiply the whole equation by -3
2v +6w = -36 Add both equations
-15v -6w = -3
--------------------------
-13v = -39 Divide both sides by -13
v= 3
2.2) Now we can plug v= 3 in any of these equations, usually the simplest one. So let's plug into the 1st equation:
2v +6w = -36
2(3) + 6w = -36
6 + 6w = -36
6w = -36 -6
6w = -42 Divide both sides by 6
w = -7
3)Hence, the solution for this system is v = 3 and w = -7